Maternal UHRF1 Is Essential for Transcription Landscapes and Repression of Repetitive Elements During the Maternal-to-Zygotic Transition - Wu, Yanqing; Dong, Juan; Feng, Shenglei; Zhao, Qiang; Duan, Peng; Xiong, Mengneng; Wen, Yujiao; Lv, Chunyu; Wang, Xiaoli; Yuan, Shuiqiao (Frontiers in Cell and Developmental Biology, 2021)
Maternal factors that modulate maternal-to-zygotic transition (MZT) are essential for the growth from specialized oocytes to totipotent embryos. Despite massive studies that have continued, the mechanisms of regulating epigenetic reprogramming during MZT remained largely elusive. UHRF1 has been studied as a critical maintainer of GC methylation in oocytes and early embryos. However, little knowledge has been acquired about its role in mouse MZT. Here, we explore the function of maternal UHRF1 in zygotic genome regulation during early mouse embryonic development. We show that conditionally knockout (cKO) of UHRF1 in either primordial or growing oocytes caused infertility but differentially affected early embryonic development. UHRF1 deficiency in primordial oocytes led to early embryonic developmental arrest at the 2-cell stage, accompanied by dramatic alterations in global DNA methylation and H3K4me3 methylation patterns. In comparison, the ablation of UHRF1 in growing oocytes resulted in a significantly lower developmental competence from 2-cells to blastocysts. At the transcriptional level, the absence of maternal UHRF1 led to aberrant transcriptional regulation of the zygotic genome during the maternal-to-zygotic transition, at the 2-cell stage. Furthermore, we observed the retrotransposable elements in UHRF1-deficient oocytes and embryos failed to be properly silenced, especially the LINE-1 and LTR subfamily were activated abnormally. Collectively, our study reveals maternal UHRF1 plays a critical novel role in establishing the correct epigenetic chromatin reprogramming of the early embryos, regulating essential genes during MZT, and preserving genome integrity that drives early mouse development.